(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluating the memory enhancing effect of Hup A soft capsules using the scopolamine model. Subject: The product used in the study is Hup A soft capsule, Enterprise standard. Methods:Mice were given Hup A at doses of 192mg and 384mg/kg/24h, then injected intraperitoneally (i.p) with 1.5 mg/kg/24h Scopolamine (Scop). Mice were tested on the Y-maze and the Morris water maze. Results: Frequency and percentage of alternation of treatment dose 2 had much higher values than Scop (p<0.05). Glantamine (Galan) group and treatment dose 1 had higher values than the control group but not statistically significant (p>0.05). The time taken for mice to swim when finding a platform at 7th day in treatment groups 1 and 2, the Galan group, decreased differently compared to the Scop group (p<0.05). Mice receiving Hup A for 21 consecutive days with dose 2 increased their swimming time at the dock compared to the Scop group (p<0.05) and was equivalent to the control group (p>0.05). Conclusion: Mice given Hup A soft capsules have the effect of enhancing memory by increasing the frequency of alternating turns, reducing the time it takes mice to swim to find the platform and increasing the swimming time at the platform.